Spasmodic Muscle Cramps and Wilson Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Ann & Robert H. Lurie Children's Hospital of Chicago report a case of Wilson disease (WD) in a 10-year-old-boy presenting with 3 months of increasingly severe spasmodic muscle cramps and weakness in lower extremities, upper extremities, and cramps in face and chest.